2007
DOI: 10.1590/s1516-31802007000300004
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative warming combined with intraoperative skin-surface warming does not avoid hypothermia caused by spinal anesthesia in patients with midazolam premedication

Abstract: CONTEXT AND OBJECTIVE: Inadvertent perioperative hypothermia is common during spinal anesthesia and after midazolam administration. The aim of this study was to evaluate the effects of intraoperative skin-surface warming with and without 45 minutes of preoperative warming in preventing intraoperative and postoperative hypothermia caused by spinal anesthesia in patients with midazolam premedication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 31 publications
(69 reference statements)
0
16
0
1
Order By: Relevance
“…Pre-operative warming has also been tried. 2,5,7 In this study, we wanted to evaluate a new thermal suit in peri-operative thermal care of patients. Thermal suits have been developed for emergency care in order to reduce thermal loss of injured patients during transportation, but, as far as we are aware, the suit evaluated in our study is the first thermal suit developed especially for use during surgical procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Pre-operative warming has also been tried. 2,5,7 In this study, we wanted to evaluate a new thermal suit in peri-operative thermal care of patients. Thermal suits have been developed for emergency care in order to reduce thermal loss of injured patients during transportation, but, as far as we are aware, the suit evaluated in our study is the first thermal suit developed especially for use during surgical procedures.…”
Section: Introductionmentioning
confidence: 99%
“…In both groups, variations concerning RT were considered clinically significant, indicating the onset of mild hypothermia, characterized in the canine species by temperatures between 32º and 37ºC, as reported by Armstrong et al 9 Such alterations may be explained by peripheral vasodilatation and reduced thermoregulatory vasoconstriction, which occur after induction of general anesthesia, even so in this case such loss has overcome the 1.5ºC decrease in the first 60 minutes due to thermal redistribution of central temperature, as mentioned by Deakin 1 and Vanni et al 2 Another factor directly related to the results relates to the operating room temperature, established at 22 ºC, which contributed for the patients' heat loss, since room temperature is, as quoted from Vanni et al 2 a known predictor of central temperature in anesthetized patients. As said those authors, assays considering average temperature in operating rooms, 20º to 23º C, revealed and average of 50% of hypothermic humane patients, despite pre and/or trans operative heating.…”
Section: Discussionmentioning
confidence: 81%
“…The experiment was carried out after submission and approval by The Committee of Ethics in Research of Federal University of Goias, under the guidelines of ethics and animal welfare, in an operating room acclimatized at 22º C, as suggested by Bernard et al 5 and Vanni et al 2 Thirteen bitches of several breeds, with mean body weight Mean arterial pressure (MAP) was invasively assessed by canulating the femoral artery and using an aneroid manometer, as described by Rezende et al 7 , from M30 on, 15 minutes after anesthetic induction.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations